Play in Asian preschools? Mapping a landscape of hindering factors. (December 2021) - Bautista, Alfredo; Yu, Jimmy; Lee, Kerry; Sun, Jin
This article investigates the variety of factors that hinder the implementation of play (as defined by western scholars) in Asian preschools. Drawing on the theoretical frameworks of policy borrowing, enactment and glocalisation, we analyse three jurisdictions that illustrate distinctive problematics: India, Mainland China and Hong Kong. The methodology involves a bibliographic review. Each jurisdiction is presented as a narrative portrait, including key sociocultural characteristics, features of early childhood education system, role of play in government policies, and teachers' beliefs and practices pertaining to play. The findings show that the distinctive factors hindering play relate to societal mindsets in India, a lack of curriculum clarity in China, and structural factors and parental pressures in Hong Kong. Common hurdles include a high societal emphasis on academic learning, lack of information on how play should contribute to achieve curriculum outcomes, and insufficient teacher preparation. The authors show that play is neither adequately defined nor justified in some Asian policy frameworks, and argue that play might not be viable in certain preschools (especially in half-day programmes). An alternative glocal notion is proposed – child-led activities – which would be less conceptually problematic and more culturally appropriate. The study highlights the need for the glocalisation of Asian early childhood education systems.